Obserwowanie cierpienia? O traumatyczności doświadczeń dzieci i zwierząt związanych z polowaniami na podstawie wybranych utworów literackich - Naplocha, Anna (Zoophilologica. Polish Journal of Animal Studies, 2018)
The paper deals with the problem of traumatic experiences of children and animals related to hunting from the point of view of animal studies. The subject of hunting covers usually only the ethical side of this hobby. In the defense of animals which are the object of hunting activities, the emphasis is mainly on human interference in the law of nature and its influence on reducing the local wildlife population. The article presents a topic related to the psychological aspect of hunting, which is often overlooked in the general social discourse. The subject of the survey was to present one of the aspects of the human psyche – traumatic experience as the influence of hunting on the participating children. Based on selected examples of literary works on hunting the impact of those traumatic experiences of children is outlined. The effects of traumatic experiences and the situations of transferring the trauma from one’s experience and considering it as its own are presented. In addition, the article presents the problems of traumatic experiences in animals and their suffering not only related to the somatic but also to the psychic side. Based on ethology, the hunting influence on mental suffering animals is shown with particular emphasis on those which live in the herd. The issues presented in the article are testimony to the similarity of humans and animals’ mental experiences in humans and animals.